Transitioning to residency: a qualitative study exploring residents’ perspectives on strategies for adapting to residency - Gerbrich Galema; Jasperina Brouwer; Tineke Bouwkamp-Timmer; Debbie A. D. C. Jaarsma; Götz J. K. G. Wietasch; Robbert R. J. Duvivier (BMC Medical Education)
Abstract Background The transition to residency (TTR) goes along with new opportunities for learning and development, which can also be challenging, despite the availability of preparation courses designed to ease the transition process. Although the TTR highly depends on the organization, individual combined with organizational strategies that advance adaptation are rarely investigated. This study explores residents’ strategies and experiences with organizational strategies to help them adapt to residency. Methods We conducted a template analysis of interview transcripts with 16 second-year residents from different hospital-based specialties in the Netherlands. To identify residents’ perceptions of their own and other healthcare professionals’ strategies, our template consisted of the individual and organizational strategies originating from the Organizational Socialization theory. Results Residents employed five individual strategies: observing, asking questions, establishing social relationships, and seeking information. These strategies helped them learn their tasks, appropriate behaviors, and integrate into their teams. On the organizational side, residents experienced six strategies, mapped through Organizational Socialization theory. Collective-individual: whether the residents felt they were treated as a group or as individuals. Formal-informal: whether the introduction period was formal, structured and explicit, or implicit and unstructured. Sequential-random: whether guidance was aligned with training levels or approached inconsistently. Fixed-variable: whether the residency program followed a fixed timeline or a flexible structure. Serial-disjunctive whether role models or experienced professionals were available for guidance or not. Investiture-divestiture: whether the healthcare team embraced residents’ individuality or emphasized residents’ conformity to norms. Factors influencing TTR included individual strategies, such as establishing social relationships, and organizational strategies, particularly interactional (relationships with healthcare professionals) and systemic strategies (training program structure). Residents’ perceptions varied on whether these strategies facilitated or hindered their TTR. Conclusion TTR involves dynamic interactions between residents and healthcare professionals, bridging individual and organizational strategies. This largely unexplored interaction adds a new dimension to Organizational Socialization theory. Importantly, residents' perceptions of these strategies varied: some thrived with independence, while others needed structured guidance. This suggests that residency programs should customize support to individual needs, balancing support and autonomy to improve transitions and enhance training.